FoxO1 integrates direct and indirect effects of insulin on hepatic glucose production and glucose utilization - O-Sullivan, InSug (Nat Commun, 2015)
FoxO proteins are major targets of insulin action. To better define the role of FoxO1 in mediating insulin effects in the liver, we generated liver-specific insulin receptor knockout (LIRKO) and IR/FoxO1 double knockout (LIRFKO) mice. Here we show that LIRKO mice are severely insulin resistant based on glucose, insulin and C-peptide levels, and glucose and insulin tolerance tests, and genetic deletion of hepatic FoxO1 reverses these effects. (13)C-glucose and insulin clamp studies indicate that regulation of both hepatic glucose production (HGP) and glucose utilization is impaired in LIRKO mice, and these defects are also restored in LIRFKO mice corresponding to changes in gene expression. We conclude that (1) inhibition of FoxO1 is critical for both direct (hepatic) and indirect effects of insulin on HGP and utilization, and (2) extrahepatic effects of insulin are sufficient to maintain normal whole-body and hepatic glucose metabolism when liver FoxO1 activity is disrupted.